Preparation and Application of Nanocellulose in Removing Lead from Aqueous Solutions - Hassan Tawfeeq Hassan Yassir; Ali Hussein Fadhil Sdawi; Fatima Rashid Khader Rashid; Zaid Jawad Kazem Mohammed; Fatima Basim Mahdi Mutlak (American Journal of Biodiversity, 2025)
The organic nanocellulose was prepared from starch by following the green chemistry methodology, adopting biomass as a natural source of organic nanomaterials. The prepared nanocellulose with its three different sources (laboratory starch, commercial starch, starch extracted from biomass (potato)) showed a high ability to remove exceeding (70%) with a short treatment time (only one hour), which indicates the high ability of nanocellulose to disperse and highly adsorb lead ions and include them between its folds or its long continuous chains composed of glucose units linked by 1-4 glycosidic bonds. It is worth noting that there is a high density of protons (H+) on the chemical structure of the nanocellulose chains carried on oxygen atoms in the form of hydroxyl groups (H-O-) which have a high ability to exchange and replace lead ions instead of them to form (Pb-O-) bonds, and this replacement and chemical adsorption of lead ions continues until saturation with it. The difference in the highest ability to remove lead followed the following sequence: Nanocellulose from the laboratory starch source < nanocellulose from the biomass source < nanocellulose from the commercial starch source This is simply due to the high purity of the nanocellulose from the laboratory starch source, while the purity of the nanocellulose from the biomass source was slightly less than it, but the difference was clear with the nanocellulose from the commercial starch source and what it contains of materials, the most important of which is lignin or pectin that has the ability to gelatinize when mixed with water, thus reducing the amount of free protons on the surface of the prepared nanocellulose.